PENINGKATAN PRESTASI BELAJAR IPS MELALUI MODEL PEMBELAJARAN KOOPERATIF MAKE A MATCH PADA SISWA KELAS IV SDN HARJOWINANGUN 01, TERSONO BATANG (Improving Social Science Achievement through Make A Match Cooperative Learning Model at Students of Year IV Ha (Jurnal Kreatif : Jurnal Kependidikan Dasar, 2010)
Social science achievement on diversity of ethnic and culture at semester I academic year 2010/2011 was still low. They got average score 61.10 out of 15 students, 7 male and 8 female students. Based on their avhievement, only 7 students had achieved passing grade score (6.5), whereas the average score should have been 6.5. This was because the teacher often applied explanation method during the process of teaching and learning on social science for students of year IV, and he/she had not used innovative learning model so that the students felt bored. To overcome this problem, the researcher tried to apply Make A Match Cooperative Learning Model. The subject of the research were the students of year IV, consisting of 15 students. This was a classroom action research with 3 cycles, and each cycle consisted of planning, acting, observing and  reflecting. The instruments used in this research were test items, observation sheet, interview, and documentation. The results of the research were (1) teacher’s activity at the first cycle was 66% with good qualification, second cycle was 79.54% with good qualification, and at the third cycle was 93.18% with very good qualification. The next result were (2) students’ activity at the first cycle was 60.44% with fair qualification, second cycle was 79.33% with good qualification, and third cycle was 85.77% with very good qualification. Almost all students had achieved passing grade score (6.5) at each cycle significantly and they had obtain completeness of study achievement.   At the first cycle, the average score was 67.73 with good qualification, second cycle was 73.20 with good qualification, and at the third cycle was 82.06 with good qualification. It is suggested that all the teacher conduct teaching and learning process using Make A Match Cooperative Learning Model for other lessons. It is also important to do the further research. Keywords: improving, social science achievement, make a match cooperative learning model.